Muscle strength in athletes-hand kettlebell sport for different meteorological situations - Kulthickiy Z.I (Kharkov National Pedagogical University, 2011)
Considered indicators of the strength of muscles of hands of students of general physical training and weightlifting athletes. The study involved 16 students of general physical training, 16 weightlifting athletes (III level) and 16 athletes (II level). Age 18-23 years of study (men). Investigations were carried out at meteorological situations I and type III. It is established that muscle strength depends on the athletes and sports category varies for different types of weather. When the type III weather in all surveyed groups of athletes, a decrease of muscle strength.